JOB-RELATED STRESSORS, EMPLOYEES' PERSONAL AND ORGANISATIONAL FACTORS AS PREDICTORS OF JOB PERFORMANCE IN THE CIVIL SERVICE OF OYO STATE, NIGERIA (2014)
The civil service job performance profile revealed arrays of complacency and absenteeism. This problem has been attributed partially to a mismatch in job demands, work environment, and individual abilities and behavioural pattern. Previous studies have focused on each isolated effects rather than on the multivariate impacts of the combination of these predisposing factors. This study, therefore, examined the prediction of job-related stressors, employees’ personal and organisational factors on job performance in the civil service of Oyo State, Nigeria. The survey research design was adopted. The combination of proportional, purposive, stratified and simple random sampling techniques was used in selecting 1867 civil servants (342 cadre 13 and above, 657 cadre 7- 12 and 870 cadre 1- 6) based on the size of the 10 ministries, seven departments and five agencies used. Job- Related Stressors Questionnaire (r=0.80), Employees’ Personal Factors Scale (r=0.89), Organisational Factors Scale (r=0.84) and Civil Servants’ Performance Rating Scale (r=0.76) were used to collect information from the respondents. These were complemented with 18 sessions of Indepth Interviews with civil servants; three each across the three cadres in two ministries, departments and agencies respectively. Two research questions were answered and four hypotheses tested at 0.05 significance level. Data were analysed using descriptive statistics, Pearson’s product moment correlation, t-test, multiple regression and content analysis. Job-related stressors, employees’ personal and organisational factors had a positive significant prediction on civil service job performance in Oyo State (F(13, 1848)=83.376) and contributed 36.5% to its variance. Their relative contributions were: employees’ personal factors (β=0.11), organisational factors (β=0.09) and Job-related stressors (β=-0.04). However, job-related stressors correlated relatively with job performance as follows: workload (r=0.23), drive for greater effectiveness (r=0.23), workpace (r=0.19) and poor job skills (r=0.16). Also employees’ personal factors correlated relatively with job performance as ranked: coping skills (r=0.46), demographic characteristics (r=0.44), work-life conflict (r=0.39) and personality traits (r=0.37). While the relative correlation of organisational factors were: organisational structure (r=0.42), changes within the service (r=0.38), reward system (r=0.37) and organisational culture (r=0.25). There were significant differences in observed performance across departments (F(6, 1855)=2.136) and ministries (F(9, 1852)=2.129) sampled. The work environment was perceived not to be flexible enough to accommodate innovations and creativity. The coping skills, abilities, traits and characteristics of individual were not taken into cognizance in assigning responsibilities. Job-related stressors, employees’ personal and organisational factors positively predicted job performance of civil servants in Oyo State. Therefore, there is the need for greater considerations for the combinations of the three factors when job schedules are assigned to civil servants. There is also the need to ensure proper fits between individuals and their work environment in order to reduce the rate of work-life conflicts.